Expresión artística para el desarrollo de competencias socioemocionales en el nivel primaria - Calle Higa, Jessy Megumi (2025)
The competitive and accelerated society in which we currently live requires citizens and professionals who seek constant development of their socio-emotional skills to respond to the demands of their environment. Therein lies the importance of developing these skills from school. In this sense, the present study aims to describe the artistic expression strategies implemented by teachers of 5th grade to develop awareness and emotional regulation in students of a public educational institution in Metropolitan Lima. This research responds to a qualitative approach of descriptive level and for the collection of information, two tutors of 5th grade of primary school were interviewed, and 4 observations were made. It should be noted that both, the theoretical foundation and the analysis of the data collected were conducted according to two categories. The first, related to the strategies of artistic expression for the development of emotional awareness and, the second, to the strategies of artistic expression that favor emotional regulation. The results of the study conclude that teachers apply this type of strategies in a transversal way in the classroom and using a wide variety of resources. However, the importance of pedagogical intentionality on the part of the teacher is highlighted so that the strategies of artistic expression really manage to favor the development of the socio-emotional competences of the students.